Response monitoring in follicular lymphoma by synchronous evaluation of minimal residual disease and diffusion-weighted MRI - Meleshko, A.N.; Kharuzhyk, S.A.; Piatrouskaya, N.A. (Experimental Oncology, 2015)
Aim: To demonstrate quantitative assessment of tumor response to treatment in patients with follicular lymphoma using parallel monitoring of minimal residual disease (MRD) and diffusion-weighted MRI (MRI-DWI) derived apparent diffusion coefficient (ADC). Materials and Methods: Two patients with follicular lymphoma were undergone synchronous evaluation of MRD and MRI-DWI at definite time points before, during and after chemotherapy. MRD level was calculated in diagnostic and follow up samples relative to the highest level of amplification of the target. Allele-specific primer for clonal IgH gene rearrangement was used as a target for real-time quantitative polymerase chain reaction (PCR). 1.5 Tesla scanner was used for MRI-DWI. The largest non necrotic lymph node was chosen for serial ADC measurement. Results: In first patient MRD reduced drastically in blood after chemotherapy but persisted at low level in bone marrow. Whole body MRI-DWI demonstrated regression of most of tumor lesions except one marginally enlarged iliac lymph node and allowed to predict tumor progression in this particular anatomical site based on low ADC value after treatment. In the second patient all three methods (MRD, ADC and radiologic evaluation) gave concordant result of complete tumor response and patient remained in a clinical remission during follow-up time. Conclusion: Quantitative PCR measurement may detect very low level of MRD in patients with follicular lymphoma which may have prognostic value. Combination of both PCR-based MRD and quantitative evaluation of MRI-DWI derived ADC provides safe added-value disease monitoring in lymphoma. Key Words: follicular lymphoma, minimal residual disease, diffusion-weighed MRI, apparent diffusion coefficient, response monitoring.